2020
DOI: 10.1002/ece3.6368
|View full text |Cite
|
Sign up to set email alerts
|

Ignoring non‐English‐language studies may bias ecological meta‐analyses

Abstract: Meta‐analysis plays a crucial role in syntheses of quantitative evidence in ecology and biodiversity conservation. The reliability of estimates in meta‐analyses strongly depends on unbiased sampling of primary studies. Although earlier studies have explored potential biases in ecological meta‐analyses, biases in reported statistical results and associated study characteristics published in different languages have never been tested in environmental sciences. We address this knowledge gap by systematically sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
136
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(137 citation statements)
references
References 30 publications
1
136
0
Order By: Relevance
“…Database materials are available at DOI 10.5281/zenodo.3964895 (see Data availability) 10 . Field names and descriptions from the database (filename `events-db.csv`) are detailed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Database materials are available at DOI 10.5281/zenodo.3964895 (see Data availability) 10 . Field names and descriptions from the database (filename `events-db.csv`) are detailed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…208 ProMEDmail texts passed this screening, contributing to a total of 1,791 total articles from PubMed, Embase, and ProMEDmail selected for review. Further details on the reproducible screening workflow are available in the data repository (see Data availability) 10 .…”
Section: Abstract and Report Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is widely recognized that exclusion of grey literature and unpublished data can impact on meta‐analytical estimates due to publication bias 8,9 . Also, it has been shown that if relevant non‐English‐language literature is omitted during literature searches, different meta‐analytical inferences could be drawn due to language bias 10‐12 . Such empirical evidence suggests that if meta‐analytical reviewers intentionally or unintentionally sample primary studies in a selective way during literature searches (eg, collect only studies from commercially published articles or those published in English‐language), meta‐analyses are expected to provide potentially biased estimates of overall effects.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 15, 2020. ; https://doi.org/10.1101/2020.08.13.20165852 doi: medRxiv preprint systematically missing from the database for countries that are not English speaking and/or have less health care monitoring and reporting capacity, including those with lower GDP. Therefore, it is imperative that any analysis of the data account for the effects of reporting bias 21 .…”
mentioning
confidence: 99%